Adaptation of the least squares method for determination of oscillating type measuring devices parameters with using gain-frequency characteristic - Zakharov, I. P.; Serhiienko, M. P. (My University, 2019)
In this article there is suggested a method, which determines both a time constant and a gain-frequency characteristic damp constant for a measuring device, which is simulated by oscillating type dynamic element. The described method is based on a method of least squares, which increases an identification accuracy because of obtaining more information about a measuring device performance during a measurement process. The standard uncertainties of both a time constant and a damp constant are analyzed. The recommendations for measuring process, which was mentioned above, optimization are given.
Keywords: measuring device; oscillating type dynamic element; dynamic characteristic; gain-frequency characteristic; standard uncertainty